Malnutrition assessment methods in adult patients with tuberculosis: a systematic review - Huib A M Kerstjens; Tjip S van der Werf; Jan-Willem C Alffenaar; Simon Tiberi; Lies ter Beek; Mathieu S Bolhuis; Harriët Jager-Wittenaar; René X D Brijan; Marieke G G Sturkenboom; Wiel C M de Lange; Onno W Akkerman (BMJ Open)
Objectives Malnutrition is associated with a twofold higher risk of dying in patients with tuberculosis (TB) and considered an important potentially reversible risk factor for failure of TB treatment. The construct of malnutrition has three domains: intake or uptake of nutrition; body composition and physical and cognitive function. The objectives of this systematic review are to identify malnutrition assessment methods, and to quantify how malnutrition assessment methods capture the international consensus definition for malnutrition, in patients with TB.Design Different assessment methods were identified. We determined the extent of capturing of the three domains of malnutrition, that is, intake or uptake of nutrition, body composition and physical and cognitive function.Results Seventeen malnutrition assessment methods were identified in 69 included studies. In 53/69 (77%) of studies, body mass index was used as the only malnutrition assessment method. Three out of 69 studies (4%) used a method that captured all three domains of malnutrition.Conclusions Our study focused on published articles. Implementation of new criteria takes time, which may take longer than the period covered by this review. Most patients with TB are assessed for only one aspect of the conceptual definition of malnutrition. The use of international consensus criteria is recommended to establish uniform diagnostics and treatment of malnutrition.PROSPERO registration number CRD42019122832.